The works of President Edwards: with a memoir of his life - Edwards, Jonathan (Samuel Miller library., 1829)
I. Life of President Edwards. Farewell sermon. Appendix: A-G. Notes. H. "The mind." I. Notes on natural science. K. Family and descendants of President Edwards. L. Catalogue of President Edwards' works, heretofore published.--II. Inquiry into the freedom of the will. The great Christian doctrine of original sin defended.--III. Dissertation on the end for which God created the world. Dissertation on the nature of true virtue. History of the work of redemption. An attempt to promote explicit agreement and visible union of God's people in extraordinary prayer. Distinguishing marks of a work of the Spirit of God.--IV. Narrative of surprising conversions. Thoughts on the revival in 1740. Qualifications for communion. Reply to Williams.--V. A treatise concerning religious affections. Justification by faith alone. Pressing into the kingdom of God. Ruth's resolution. Justice of God in the damnation of sinners. The excellency of Jesus Christ.--VI. Twenty sermons. Practical sermons.--VII. Eight sermons. Miscellaneous theological observations. Miscellaneous remarks on important theological subjects.--VIII. Seventeen occasional sermons. Miscellaneous observations.--IX. Types of the Messiah. Notes on the Bible.--X. Memoirs of the Rev. David Brainerd.